2009
DOI: 10.1158/1055-9965.epi-09-0097
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Cytoplasmic Localization of SAM68 Is a Significant and Independent Prognostic Marker for Renal Cell Carcinoma

Abstract: Purpose: This retrospective study aimed to examine the expression and localization of SAM68 (Src-associated in mitosis, 68 kDa) in a larger cohort of surgical specimens of renal cell carcinoma and their correlation with the progression of human renal cell carcinoma. Experimental Design: The protein and mRNA expression levels of SAM68 in normal renal tubular epithelial cells, renal cell carcinoma cell lines, as well as nine pairs of renal cell carcinoma and matched tumor-adjacent renal tissues were examined usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 44 publications
4
59
0
1
Order By: Relevance
“…Increased expression of Sam68 correlated with poor prognosis also in patients affected by renal carcinoma (Zhang et al 2009). Notably, in advanced stages of both breast (Song et al 2010) and renal (Zhang et al 2009) tumors, Sam68 was localized also in the cytoplasm.…”
Section: Role Of Sam68 In Cancermentioning
confidence: 87%
See 1 more Smart Citation
“…Increased expression of Sam68 correlated with poor prognosis also in patients affected by renal carcinoma (Zhang et al 2009). Notably, in advanced stages of both breast (Song et al 2010) and renal (Zhang et al 2009) tumors, Sam68 was localized also in the cytoplasm.…”
Section: Role Of Sam68 In Cancermentioning
confidence: 87%
“…Notably, in advanced stages of both breast (Song et al 2010) and renal (Zhang et al 2009) tumors, Sam68 was localized also in the cytoplasm. In both cases, cytoplasmic localization of the protein represented an independent factor of poor prognosis.…”
Section: Role Of Sam68 In Cancermentioning
confidence: 99%
“…Previous studies revealed that the PI3K/AKT signal transduction cascade was required for cell-cycle progression through the G 1 -phase (25). In addition, activation of PI3K/AKT decreases the cellular levels of p21Cip1 and p27Kip1, and induces cyclin D1 expression, thereby promoting cell proliferation (14,26). The modulation of these cell-cycle regulators by PI3K/AKT is accomplished either directly or indirectly through inhibiting the phosphorylation and activation of FOXO3a (14,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…PHLPP1 and PHLPP2 belong to a novel family of Ser/Thr protein phosphatases and play central roles in maintaining cell survival suppression through negatively regulating the signaling pathways activated by AKT, PKC, MAPK, and Mst1 (29)(30)(31)(32). Evidence has recently emerged to suggest that PHLPP1 and PHLPP2 act as tumor suppressor genes, and their expression is frequently depleted in a variety of human cancers, including breast cancer, prostate cancer, and colorectal cancer (26,33). As Ser/Thr protein phosphatases, PHLPP1 and PHLPP2 can directly dephosphorylate AKT to inhibit AKT signaling activity, which promotes apoptosis (15,30,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation